(untitled) (Actualizaciones en Sida e Infectología, 2022)
Monkeypox virus is an orthopoxvirus with zoonotic characteristics endemic in Central and West Africa regions, where it has caused outbreaks since 1970. An exponential increase in cases has been registered in the last decades, probably associated with a decrease in the immunity conferred by the smallpox vaccine, discontinued after smallpox eradication. In recent years, sporadic cases have been reported outside the African continent, always epidemiologically related to permanence in endemic areas or contact with infected animals. Since May 13, 2022, the largest monkeypox outbreak ever reported outside Africa endemic areas, with cases on the five continents, is unfolding. The extent, impact and duration of this outbreak still remain uncertain..